Comunidades quilombolas do Portal do Sertão da Bahia : direito, território e identidade - Santos, Jucélia Bispo dos (2014)
This research analyzes situations of recognition of Quilombola communities in Portal do Sertão da Bahia territory, from the implementation of article 68 of the Constitution and Decree No. 4887/2003, which acknowledge the quilombola identity through the criterion of self-declaration. After the creation of new public policies for quilombolas, some black communities of the Portal do Sertão da Bahia sought recognition. Currently, there are eight Quilombola communities recognized in this region:Paus Altos e Gavião (Antônio Cardoso); Massaranduba, Tapera Melão, Olaria, Pedra Branca e Baixinha (Irará); Lagoa Grande (Feira de Santana); Bete II (São Gonçalo). The memory of quilombos was stimulated from 2008, aiming at building the self-declaration of the quilombola community. Groups have been organized due to the meetings of residents ' Association and of the Catholic Pastoral. At that moment, the tricks of memory and the speeches were used for ethnic recognition and thus articulated the local government and Community citizens. Thus, the discourse of ethnicity was specified as a source of meaning of identity within a perspective of engagement. Such discursive constructions built new cultural codes from the material provided by history and by political engagement. Through the fieldwork carried out in Olaria community, in Irará (BA), it has been sought to address the re-reading of historical experience of resistance by black communities after State legislation that give them new rights. Thus, there has been emphasis on speeches that are associated with the conception of knowing/power, involving in the realization of new political projects. In the analysis of these speeches it is possible to perceive certain manipulation relating to conceptions of justice, rights and narrative of quilombolas memories.